The Application of Unmanned Aerial Vehicle (UAV) For Slope Mapping at Gambang Damai Residents, Pahang: A Case Study - M. F., Zolkepli; M. F., Ishak; S., Daud (Penerbit UTHM, 2023)
This paper highlights the work of slopemapping utilizing the unmanned aerial vehicle (UAV) with its perimeter, area, and volume of particular regions chosen at Gambang Damai Residents in Kuantan Pahang. The location selected was choose because of its proximity to the study area. Slope mapping has traditionally been time-consuming and challenging, especially in hilly areas. This research also aimed to identify potential slope hazards based on slope angle. The accuracy and nature of typical mapping outputs, such as the Digital Elevation Model (DEM) and Digital Orthophoto, depend on high-quality photos that modern UAVs can only capture. These photographs taken by the UAV will be transferred to Agisoft software to generatea complete map of the study area. With the help of Global Mapper, it's easy to measure elements such as the perimeter, area, and volume of selected study areas, which is the main point of this research. The results of the two slopes (slope A and slope B) show that slope B produces a massive volume of 1469.7 m3, whilst slope A generates just 1382.9 m3. Slope A has an enclosed area of 1634.3 m2, which is more significant than slope B's enclosed area of 766.86 m2.Additionally, slope A's perimeter is 162.28 m, more extensive than slope B's 159.45 m. Another result of this research is that researchers and engineers may evaluate potential slope hazards using a contemporary mapping approach by determining their particular slope angles. According to the findings, slope A has an angle of 47.35⁰, while slope B has an angle of 54.75⁰. Both slopes considered to be very steep. In conclusion, using current technology, such as UAVs, is quite beneficial when mapping in geotechnical engineering. Researchers and engineers can gather slope measurements more quickly than with previous traditional approaches by adopting multi-rotor UAV slope mapping.